2015
DOI: 10.1038/srep15005
|View full text |Cite
|
Sign up to set email alerts
|

Density-gradient centrifugation enables the purification of cultured corneal endothelial cells for cell therapy by eliminating senescent cells

Abstract: The corneal endothelium is essential for maintaining corneal transparency; therefore, corneal endothelial dysfunction causes serious vision loss. Tissue engineering-based therapy is potentially a less invasive and more effective therapeutic modality. We recently started a first-in-man clinical trial of cell-based therapy for treating corneal endothelial dysfunction in Japan. However, the senescence of corneal endothelial cells (CECs) during the serial passage culture needed to obtain massive quantities of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…A total of four human donor corneas (from persons >40 years of age) were used for cultivation of HCECs by the protocol described previously. 19 Briefly, Descemet's membranes containing the HCECs were stripped from donor corneas, and the membranes were digested with 1 mg/mL collagenase A (Roche Applied Science, Penzberg, Germany) at 378C for 12 hours. The HCECs were seeded in 1 well of a 48-well plate coated with laminin E8 fragments (iMatrix-511; Nippi, Inc., Tokyo, Japan) (0.5 lg/cm 2 ).…”
Section: Cell Culturementioning
confidence: 99%
“…A total of four human donor corneas (from persons >40 years of age) were used for cultivation of HCECs by the protocol described previously. 19 Briefly, Descemet's membranes containing the HCECs were stripped from donor corneas, and the membranes were digested with 1 mg/mL collagenase A (Roche Applied Science, Penzberg, Germany) at 378C for 12 hours. The HCECs were seeded in 1 well of a 48-well plate coated with laminin E8 fragments (iMatrix-511; Nippi, Inc., Tokyo, Japan) (0.5 lg/cm 2 ).…”
Section: Cell Culturementioning
confidence: 99%
“…Recently, we have demonstrated that transplanted CECs of low cell density could regenerate corneal endothelium, but the cell density of the regenerated corneal endothelium was lower than that of the eye transplanted with high cell density CECs in a rabbit corneal endothelial dysfunction model. 18 These results suggested that obtaining high cell density CECs is essential for good prognosis after tissue engineering therapy.…”
Section: Discussionmentioning
confidence: 87%
“…However, the in vitro expansion of HCECs proved surprisingly difficult and we often had an insufficient number of cells with adequate cell quality for clinical use. 18 HCECs are difficult to maintain under culture conditions, and even if they survive, they show limited proliferative ability and undergo massive fibroblastic transformation with loss of functional phenotypes. Consequently, our research group and others have continuously strived to develop a successful culture method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 To investigate the effect of culture protocols on morphologic differences in cultured HCEnCs, a series of primary cultures from different donors were investigated. Morphologically distinct subpopulations of highly uniform cells growing in colony-like structures, interspersed among largely nonproliferative and senescent primary cells, were detected in representative normal corneas from a 21-year-old man, 56-year-old man, and 70-year-old man (HCEnC-21M, HCEnC-56M, and HCEnC-70M, respectively) (Figure 1, AeC).…”
Section: Identification Of Highly Proliferative Cell Colonies From Nomentioning
confidence: 99%